1982
DOI: 10.2134/jeq1982.00472425001100010006x
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa Hay Grown with Municipal Waste Water and Pump Water

Abstract: The influence of municipal waste water on the growth and yield of alfalfa (Medicago sativa L.) was studied in field experiments near Buckeye, Ariz., in 1974 and 1975. The crop was planted in October of each year at a seeding rate of 22.4 kg/ha (20 lb/acre). Approximately 150 cm (60 in) of irrigation water were applied in flood irrigations each year. The response of alfalfa to two irrigation treatments: (i) pump water from local wells (control) and (ii) municipal waste water from Phoenix and pump water in a 50:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…There was no deleterious effect of the beverage industry effluent on the quality of sunflower oil due to beverage industry effluent. Day et al, (1982) reported that wheat grain quality was not affected by sewage effluent irrigation. Similar observations were reported by Mohan Singh et al, (1993), Babu et al, (1996) and Sharma et al, (2011).…”
Section: Quality Of Sunflower Cropmentioning
confidence: 99%
“…There was no deleterious effect of the beverage industry effluent on the quality of sunflower oil due to beverage industry effluent. Day et al, (1982) reported that wheat grain quality was not affected by sewage effluent irrigation. Similar observations were reported by Mohan Singh et al, (1993), Babu et al, (1996) and Sharma et al, (2011).…”
Section: Quality Of Sunflower Cropmentioning
confidence: 99%
“…Preliminary work has also been reported on the irrigational utility of petrochemical wastewater (Schmidt et al 1975;Al-A'ama and Nakhla 1995;Aziz et al 1995;Sastry and Sundaramoorthy 1996;Hussain et al 2002). Some works have been done on the performance of a few crops irrigated with wastewaters discharged from various sources (Day et al 1979;Chakrabarti and Chakrabarti 1988;Greene et al 1980;Day et al 1981;Reddy et al 1990;Herpin et al 2007). The present study was designed to attain comprehensive information on the effect of treated-gas processing effluent on soil characteristics temporally and to assess its suitability as an alternate source of fresh water irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Land application of degraded water has been widely regarded as an effective option to reduce fresh water amount used for agricultural and municipal irrigation (Thomas et al, 2006). For example, treated municipal wastewater has been successfully land-applied to grow crops and turfgrass (Day et al, 1962(Day et al, , 1982Day and Kirkpatrick, 1973;Duan et al, 2011;Mancino and Pepper, 1992).…”
Section: Introductionmentioning
confidence: 99%